Durable Response to Sintilimab and Chidamide in a Patient With Pegaspargase- and Immunotherapy-Resistant NK/T-Cell Lymphoma: Case Report and Literature Review - Yan, Zheng; Yao, Shuna; Liu, Yanyan; Zhang, Jianbo; Li, Peng; Wang, Haiying; Chu, Junfeng; Zhao, Shuang; Yao, Zhihua (Frontiers in Oncology, 2020)
The prognosis of patients with relapsed/refractory NK/T-cell lymphoma (NKTCL) is dismal. Immunotherapy has showed encouraging anti-tumor activity in patients with asparaginase-resistant NKTCL; however, only a portion of patients benefit and the median response duration is rather short. Treatment strategies have not been identified for immunotherapy-resistant NKTCL. We describe a patient with primary cutaneous NKTCL experienced disease progression after pegaspargase-based chemotherapy and PD-1 inhibitor (sintilimab)-based immunotherapy. Following a combined treatment of sintilimab and the HDAC inhibitor chidamide, the patient achieved a durable complete molecular response with mild toxicity. This case indicates that the combination of PD-1 inhibitor and HDAC inhibitor might be a treatment choice for immunotherapy-resistant NKTCL.